Visualization of Protein Sorting at the Trans-Golgi Network and Endosomes Through Super-Resolution Imaging - Huang, Yan; Ma, Tianji; Lau, Pik Ki; Wang, Jinhui; Zhao, Teng; Du, Shengwang; Loy, Michael M. T.; Guo, Yusong (Frontiers in Cell and Developmental Biology, 2019)
The trans-Golgi network (TGN) and endosomes are essential protein sorting stations in the secretory transport pathway. Protein sorting is fundamentally a process of spatial segregation, but the spatial relationships among the proteins that constitute the sorting machinery have not been systematically analyzed at high resolution in mammalian cells. Here, using two-color STORM imaging, we show that the TGN/endosome-localized cargo adaptors, AP-1, GGA2 and epsinR, form elongated structures of over 250 nm in length at the juxta-nuclear Golgi area. Many of these structures are associated with clathrin. We found that AP-1 is spatially segregated from AP-3 and GGA2, whereas a fraction of AP-1 and GGA2 punctae are associated with epsinR. Moreover, we observed that the planar cell polarity cargo proteins, Vangl2 and Frizzled6 associate with different cargo adaptors – AP-1 and GGA2 or epsinR respectively – when exiting the TGN. Knockdown analysis confirms the functional significance of this segregation. Our data indicates that TGN/endosome-localized cargo adaptors have distinct spatial relationships. The spatially segregated cargo adaptors GGA2 and AP-1 regulate sorting of Frizzled6 and Vangl2 respectively and spatially associated cargo adaptors can cooperatively regulate a specific sorting process.